Role of BgaA as a Pneumococcal Virulence Factor Elucidated by Molecular Evolutionary Analysis - Yamaguchi, Masaya; Takemura, Moe; Higashi, Kotaro; Goto, Kana; Hirose, Yujiro; Sumitomo, Tomoko; Nakata, Masanobu; Uzawa, Narikazu; Kawabata, Shigetada (Frontiers in Microbiology, 2020)
Streptococcus pneumoniae is a major cause of pneumonia, sepsis, and meningitis. Previously, we identified a novel virulence factor by investigating evolutionary selective pressure exerted on pneumococcal choline-binding cell surface proteins. Herein, we focus on another pneumococcal cell surface protein. Cell wall-anchoring proteins containing the LPXTG motif are conserved in Gram-positive bacteria. Our evolutionary analysis showed that among the examined genes, nanA and bgaA had high proportions of codon that were under significant negative selection. Both nanA and bgaA encode a multi-functional glycosidase that aids nutrient acquisition in a glucose-poor environment, pneumococcal adherence to host cells, and evasion from host immunity. However, several studies have shown that the role of BgaA is limited in a mouse pneumonia model, and it remains unclear if BgaA affects pneumococcal pathogenesis in a mouse sepsis model. To evaluate the distribution and pathogenicity of bgaA, we performed phylogenetic analysis and intravenous infection assay. In both Bayesian and maximum likelihood phylogenetic trees, the genetic distances between pneumococcal bgaA was small, and the cluster of pneumococcal bgaA did not contain other bacterial orthologs except for a Streptococcus gwangjuense gene. Evolutionary analysis and BgaA structure indicated BgaA active site was not allowed to change. The mouse infection assay showed that the deletion of bgaA significantly reduced host mortality. These results indicated that both nanA and bgaA encode evolutionally conserved pneumococcal virulence factors and that molecular evolutionary analysis could be a useful alternative strategy for identification of virulence factors.